Milk protein allergy--a rare cause of pyrexia of unknown origin in an adult female. Issue 761 (March 1989) - Dhar, K. L.; Gupta, B.; Adlakha, A.; Choudhrie, A. V.
Abstract : Milk protein allergy is described in a young adult female patient who presented with fever and malabsorption syndrome. The patient fulfilled Goldman's criteria for the diagnosis of milk protein allergy and responded to an elimination diet.